Pembinaan Nilai – Nilai Religius Bagi Masyarakat Pedukuhan Kubang Tegal - Nanang Lidwan; Maksum Maksum; Ery Suryanti; Puspa Fortuna Zulfa (Departement of Mathematics Education, 2024)
Education is an important factor that contributes to the country's progress at all levels of society. The extent to which religious values can influence and shape a person's character really depends on how many religious values are embedded in him. The deeper religious values are embedded in a person, the more his personality will manifest and form religious attitudes, because people are used to carrying out religious activities. Religious values are the basis for the formation of religious cultural values, because if religious values are not formed then religious culture will not be formed. This research includes field research, with a qualitative approach, meaning research that produces analytical procedures that do not use statistical analysis or other quantitative methods. The data collection techniques are interviews, observations and notes. The data obtained was then analyzed using qualitative descriptive analysis techniques. The results of this research show that the strategy for religious values for the community of Pacul village is to provide spiritual purification, holding additional activities such as maulidan activities, religious activities, visiting sick people, and other spiritual worship.